Brain cavernous hemangioma mimicking radiation‐induced necrosis in a patient with non‐small cell lung cancer. Issue 7 (29th May 2020) - Takamori, Shinkichi; Seto, Takashi; Jinnouchi, Mikako; Matsubara, Taichi; Haratake, Naoki; Miura, Naoko; Toyozawa, Ryo; Yamaguchi, Masafumi; Takenoyama, Mitsuhiro
Abstract : In patients with non‐small cell lung cancer (NSCLC), stereotactic radiotherapy (SRT) is one of the standard therapies for those suffering with intracranial metastatic NSCLC. Radiation‐induced necrosis (RIN) sometimes occurs as the result of the delayed effects of SRT. The magnetic resonance imaging (MRI) of RIN typically shows hypointense and hyperintense lesions on T1‐ and T2‐weighted images, respectively. We herein report a patient with a growing brain cystic lesion mimicking RIN adjacent to a post‐radiation brain metastasis from NSCLC harboring anaplastic lymphoma kinase rearrangement. The patient underwent surgical resection of the brain tumor because of the symptoms. The pathological diagnosis was cavernous hemangioma, and the pathological findings were an encapsulated nodular mass composed of dilated, cavernous vascular spaces with no residual tumor or recurrence. Clinicians should be aware of the possibility for the development of a brain cavernous hemangioma following SRT in NSCLC patients.